STRATEGI HUMAS UNTUK MEMPERBAIKI CITRA LEMBAGA PENDIDIKAN - Mashudi, Moh (Universitas Islam Sultan Agung, 2020)
ABSTRACTPublic relations serves as a distinctive management and supports the coaching, maintenance of the joint pathway between the organization and the public, concerning communication activities, understanding, acceptance and cooperation, involving management in dealing with problems, helping management to be able to face public opinion.Creating a positive image for an institution or education, the role of Public Relations is also involved in many things such as making strategies and programs interesting to be able to compete and still exist both in a profit-oriented institutions and services to the community or nonprofit. The success of a Public Relations will determine the success or failure of vision and mission in an education or institution.Looking at the above background contains the formulation of the problem: 1) How the public relations devinisi and research ? 2) What is the negative and positive impact of public relations in educational institutions? 3) How to Step by step analysis of persuasive and contributive strategy in developing public relations in educational institutions.The results of the theory analysis can be summarized as follows: 1) Public Relations is a typical management function, which supports coaching and maintenance, the joint path between the organization and its Public about communication, understanding and cooperation. Engage and assist management to know and respond to public opinion, establish and emphasize management's responsibility to serve the public as well as to support management in making positive use of experiments, using sound and ethical research and communication techniques as the primary means. 2) Negative influence, may occur due to ethical abuse in public relations activities and the positive influence that can result from the implementation of the code of ethics. 3) Steps - persuasive and contributive strategy in building Public Relations effectively by improving internal and external quality. So that Public Relations remain in good harmony with institutions and society.Â Keywords: Public relations Strategy, Improving Education Institution image